Uma nova espécie de Clelia (Serpentes, Colubridae) do sul do Brasil - Morato, Sérgio Augusto A.; Franco, Francisco L.; Sanches, Eros J. (Phyllomedusa: Journal of Herpetology, 2003)
Clelia hussami sp. nov. is described based on 10 specimens from southern Brazil. The new species can be diagnosed by the following arrangement of characters: 19 midbody dorsal rows, 7 supralabials and 8 infralabials, 204-225 ventrals, 47-56 paired subcaudals, ground coloration light brown with a fine dark reticulum in adults, presence of a narrow dark vertebral line and clear nucal collar more evident in juveniles, and a creamily light immaculated venter. A description of hemipenis is presented.